Poverty and Regional Development in Eastern Europe and Central Asia - Dillinger, William (Washington, DC: World Bank, 2012)
This paper is focused only on this objective: the alleviation of regional concentrations of poverty. There are several reasons. First, judging from the public documents of multilaterals and governments, poverty reduction is often the primary objective of regional development efforts in the ECA region. It is also the primary objective of the World Bank, the sponsor of this paper. Second, the environmental and social objectives of regional development are difficult to analyze through an economic lens. While some may argue that cities are too big, others argue that large cities are crucial to economic growth and merely need to be better managed. By the same token, the social costs of out-migration are difficult to weigh against the economic benefits of labor mobility. The analysis of the tradeoffs between the environmental and social objectives of regional development on one hand, and economic objectives of regional development on the other, is better done on a case-by-case basis than in a regional survey paper. This report is the first of a series of papers on regional issues in the ECA region.